2020
DOI: 10.13106/jafeb.2020.vol7.no11.629
|View full text |Cite
|
Sign up to set email alerts
|

The Determinants of Foreign Exchange Reserves: Evidence from Indonesia

Abstract: This study aims to identify and analyze the factors that affect foreign exchange reserves in Indonesia. We consider the variables of external debt, exchange rate, inflation, and exports as explanatory factors referring to previous studies. We apply the Autoregressive Distributed Lag approach to time-series data retrieved from the Central Bank of Indonesia (BI), the Central Bureau of Statistics (BPS), and International Monetary Funds (IMF) from January 2016 to December 2018. Our results show that foreign debt, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 7 publications
(8 reference statements)
7
22
0
1
Order By: Relevance
“…The relationship between the exchange rate and foreign exchange reserves is similar to several theories, as evidenced by research from Sayoga & Tan (2017) and Andriyani et al (2020), who discovered that the exchange rate had a negative and significant effect on Indonesia's foreign exchange reserves. Furthermore, this study contradicts research from (Kaligis 2017), which discovered that the exchange rate has a positive and significant effect on Indonesia's foreign exchange reserves.…”
Section: Resultssupporting
confidence: 76%
“…The relationship between the exchange rate and foreign exchange reserves is similar to several theories, as evidenced by research from Sayoga & Tan (2017) and Andriyani et al (2020), who discovered that the exchange rate had a negative and significant effect on Indonesia's foreign exchange reserves. Furthermore, this study contradicts research from (Kaligis 2017), which discovered that the exchange rate has a positive and significant effect on Indonesia's foreign exchange reserves.…”
Section: Resultssupporting
confidence: 76%
“…The positive effect indicates that increasing exports (selling items to foreign nations) will boost Indonesia's state income in foreign currency, which will then be held as foreign exchange reserves. This study supports the findings of Andriyani et al (2020) and Indriany et al (2021), all of which found that exports have a positive and significant impact on Indonesia's foreign exchange reserves. This could imply that Indonesia should pay attention to factors that have a positive impact on foreign exchange reserves, such as exports, taxes, and capital inflows, as well as limit imports of items that can be produced domestically.…”
Section: Vecm Model Regressionsupporting
confidence: 90%
“…The payment of maturing government foreign debt and attempts to stabilize currency rates amidst global financial market turmoil produced a drop in foreign exchange reserves in 2018. Exports and foreign debt have a positive and considerable effect on foreign exchange reserves, according to Antoni et al (2019) and Andriyani et al (2020). The increase or decrease in foreign exchange reserves is sometimes not in line with the increase or decrease in exports and imports.…”
Section: Introductionmentioning
confidence: 98%
“…Jena and Sethi (2020) employing ARDL-ECM with data of 1960-2018 concluded that current account balance, domestic credit of private sector, exchange rate, per capital GDP, inflation, real interest rate are long-run determinants of foreign exchange reserve in Brazil. A similar approach applied by Andriyani, et al (2020) in the case of Indonesia over the period of January 2016 to December 2018 reported that foreign debt, inflation, export, and exchange rate affect the foreign exchange reserve.…”
Section: Research Limitationsmentioning
confidence: 97%